FRI0063 Non- Neutralizing Autoantibody Against GM-CSF in Connective Tissue Diseases and its Association with Pulmonary Involvements - Nagasawa, J.; Kurasawa, K.; Tanaka, A.; Yamazaki, R.; Okada, H.; Arai, S.; Owada, T.; Maezawa, R. (Annals of the rheumatic diseases, 2015)
BackgroundGranulocyte-macrophage colony-stimulating factor (GM-CSF) is an important hematopoietic growth factor, particularly for differentiation of alveolar macrophage, and immune modulator including inflammation. Neutralizing autoantibodies against GM-CSF antibodies cause pulmonary alveolar proteinosis (PAP). We have previously reported a SLE patient with anti-GM-CSF antibody (Ab) and PAP (Lupus 2013;22, 1060). However, it remains unknown whether there exist autoantibodies against GM-CSF in connective tissue disease (CTD) patients without PAP.ObjectivesTo determine whether anti-GMF autoantibody is detected in sera from CTD patients. If so, to determine whether the antibody has neutralizing activity and to clarify the clinical features of patients with the antibody.MethodsSubjects were 245 CTD patients (SLE; 63, DM/PM; 49, RA; 106, vasculitis; 27) and 34 healthy controls. A EIA system to detect anti-GM-CSF Abs was developed; GM-CSF was coated on the plate that was then blocked with BSA, diluted serum with PBS was added, and after washing the Ab was detected by anti-IgG Ab. To avoid non-specific binding, the optic density (OD) of the Ab was calculated as follows; OD (GM-CSF coated well) -OD (GM-CSF negative well). The neutralizing activity of the Ab was examined through inhibition of CD11b expression on neutrophils by GM-CSF; neutrophils were incubated in media with GM-CSF (5ng/ml) and serum from the subjects, and CD11b expression was examined using flowcytometry. Association of clinical features with the Ab was assessed by reviewing medical records.ResultsAnti-GM-CSF Ab was detected in 60% of CTD (frequencies of positivity: SLE; 70%, DM/PM; 57%, RA; 57%, vasculitis 55%) (Fig.1). PAP was not found in all cases except one SLE that has been reported previously. Neutralizing activity was not detected except the case of SLE with PAP. Pulmonary involvements including interstitial lung disease, bronchial disease and pleuritis was frequently found in RA patients positive for the Abs compared to negative patients (positive 47%, vs negative 18%; p<0.001). Similarly, pulmonary involvements were found in SLE patients with the Abs (positive 25%, vs negative 5%; p=0. 04). In DM/PM, no differences were found in frequencies of of pulmonary involvements between the Ab positive and negative groups, because more than 80% of the patients had lung involvements.Therapy decreased titers of the Ab in SLE and RA.ConclusionsNon-neutralising Autoantibody against GM-CSF was frequently detected in CTD patients, particularly those with pulmonary involvements. These findings suggest that the autoantibody, which might work as carrier protein of GM-CSF, plays roles in the development of CTDs, especially pulmonary involvements in RA and SLE.Disclosure of InterestNone declared